Islamic finance as an alternative for financing the Algerian economy post-COVID-19 - Lotfi, Zeghbid Nassim (International journal of economic perspectives, 2024)
In this article, we focus on Islamic Finance, which offers a unique and ethical alternative for financing the Algerian economy in a post-COVID-19 scenario. This system is based on principles derived from Sharia law, such as the prohibition of interest (riba) and investment in activities deemed unethical. By adhering to these principles, Islamic Finance promotes fairness, transparency, and risk sharing between parties. In the context of Algeria post-COVID-19, Islamic Finance can help stimulate economic growth by providing access to funding for businesses and individuals while minimizing exploitative practices. This alternative form of financing can also attract foreign investment, diversify the financial sector, and promote socio-economic development. Additionally, Islamic Finance mechanisms like Mudarabah (profit sharing) and Musharaka (partnership) can foster entrepreneurship and innovation in Algeria. Furthermore, Islamic Finance emphasizes real economic activities and asset-backed transactions, which can reduce speculation and promote stability within the Algerian economy. By encouraging ethical investments in sectors such as agriculture, infrastructure, and renewable energy, Islamic Finance can contribute to sustainable development and poverty alleviation in the country. Overall, embracing Islamic Finance as a financing alternative in Algeria post-COVID-19 cannot only help rebuild the economy but also foster a more inclusive and sustainable financial system aligned with Islamic ethical principles.